2016
DOI: 10.1021/acscentsci.6b00218
|View full text |Cite
|
Sign up to set email alerts
|

Striking Plasticity of CRISPR-Cas9 and Key Role of Non-target DNA, as Revealed by Molecular Simulations

Abstract: The CRISPR (clustered regularly interspaced short palindromic repeats)-Cas9 system recently emerged as a transformative genome-editing technology that is innovating basic bioscience and applied medicine and biotechnology. The endonuclease Cas9 associates with a guide RNA to match and cleave complementary sequences in double stranded DNA, forming an RNA:DNA hybrid and a displaced non-target DNA strand. Although extensive structural studies are ongoing, the conformational dynamics of Cas9 and its interplay with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
186
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(204 citation statements)
references
References 39 publications
17
186
1
Order By: Relevance
“…The RECI region moves in the opposite direction with respect to RECIII and together with the R-rich helix, whereas the nuclease lobe remains stable (SI Appendix, Fig. S5) (7,13,24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RECI region moves in the opposite direction with respect to RECIII and together with the R-rich helix, whereas the nuclease lobe remains stable (SI Appendix, Fig. S5) (7,13,24).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we also performed TMD simulations of Cas9:precat targeted to Cas9:DNA including all nucleic acid chains (i.e., RNA, t-DNA, and nt-DNA), revealing that the presence of the nt-DNA within the RuvC groove exerts a steric constraint that hampers the structural transition of HNH (φ does not change phase). This indicates that the transition of the HNH domain is unlikely to occur after complete DNA unwinding and relocation for the catalysis, suggesting that HNH repositioning might occur during the process of doublestrand separation (7,11,13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies suggested that a domain within the Cas9 recognition (REC) lobe (REC3) interacts with the RNA/DNA heteroduplex and undergoes conformational changes upon target binding (Extended Data Figure 2e–f) 13,14,1719 . Because the function of this non-catalytic domain was previously unknown, we labeled SpCas9 with Cy3/Cy5 dyes at positions S701C (within the “mobile” REC3 domain) and S960C (within the “stationary” RuvC domain) to generate SpCas9 REC3 and observed that the conformational states of REC3 become more heterogeneous as PAM-distal mismatches increase (Extended Data Figure 4a–c).…”
mentioning
confidence: 99%
“…Structural studies suggested that REC2 occludes the HNH domain from the scissile phosphate in the sgRNA-bound state 19 , and undergoes a large outward rotation upon binding to double-stranded DNA (dsDNA) 13,14 (Figure 2e). To test whether the REC2 domain regulates access of HNH to the target strand scissile phosphate, we labeled SpCas9 with Cy3/Cy5 dyes at positions E60C (within the “stationary” Arginine-rich helix) and D273C (within the “mobile” REC2 domain) to generate SpCas9 REC2 in order to detect REC2 conformational changes (Extended Data Figure 1b–c).…”
mentioning
confidence: 99%